Probation as a Form of Professional Self-Perfection of Managers of Higher Educational Establishment - Valentine Gladkova (Pedagogical Discourse, 2012)
The article describes the features of professional self-improvement of a manager of higher educational establishment, that takes place in the form of probation. The general program of the mentioned category training of managerial staff of higher educational establishment, which is implemented in a full-time and distance forms. To ensure an effective self-perfection the system of autoprofessional competence is recommended